Literatura Mexicana del Norte - López Torres, Danira; Martínez Vela, Marlon; Sánchez Hernández, Josué (Colección Investigaciones (San Luis Potosí, Mexico), 2019)
"This work is divided into eight general sections that contemplate various approaches to the study of northern literatures, whether from some of its main themes, literary genres, some prominent elements of spatiality, such as the presence of territories, the inhospitable, aspects of temporality, about some author and his work, or, from cultural policies and the place that this literature occupies in the canon"--Latin American Book Store website